How Flagella Expression May be Regulated by the Carbon and Energy Source? - Lodeiro, Anibal (2014)
Bradyrhizobium diazoefficiens has two flagellar systems: a subpolar, constitutive system and a lateral, inducible system. Contrary to other bacterial species, the lateral system is induced in liquid medium in response to the carbon and energy source. Since both flagella are moved by the proton-motive force, a relationship between the energy status of the cell and the signal that triggers lateral flagella expression might exist. Here I discuss how this relationship may control the induction of the lateral flagellar system, and its implicancies for improvement of Bradyrhizobium-based inoculants for soybean plants.